Potensi dan Peran Pesantren dalam Mengembangkan Ekonomi Masyarakat - Moh. Wadi (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2020)
Islamic boarding schools have an important role for the independence of Indonesia and also play a role in developing the community's economy in order to assist the government in efforts to reduce poverty and unemployment. Tne example is the economic activity carried out by the Miftahul Ulum Islamic Boarding School in Panyeppen Palengaan Pamekasan. The results of the study indicate that the potential of pesantren in developing the community's economy are formal education, students, alumni, sympathizers, community and branch/affiliated madrasas. The roles and activities of Islamic boarding schools in developing the community's economy are first, by providing business capital through qarḍ al-hasan and business capital lending for people who lack and need business capital accompanied by intensive and periodic entrepreneurship training. Second, by providing job opportunities by becoming employees at economic institutions and educational institutions managed by the Al-Miftah foundation such as employees of BMT, KOIM Swalayan. Third, by providing kios for the public to be able to trade. Fourth, the provision of scholarships to outstanding students is to develop children's education. Supporting factors, namely the ideals of caregivers, empowering human resources, cooperation with other institutions and consumers are permanent and clear, while the inhibiting factors are increasingly fierce and competitive competition, limited employee knowledge, time-consuming efforts and the sudden arrival of natural risks.